Meningkatkan Kecerdasan Logis Matematis Anak Usia Dini Melalui Media Interaktif Puzzle Angka - Annisaa Nur Faudillah; Aulia Fitriani Munthe; Lu’lu Rahmadanti; Fauziah Nasution (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This study aims to examine how interactive number puzzle media can improve logical mathematical intelligence in early childhood. Using a literature review method, this study analyzed various scientific publications related to interactive media, number puzzles, and the development of logical mathematical intelligence. The results of the study indicate that logical mathematical intelligence, which includes the ability to count, understand patterns, and think systematically, can be optimized during the golden age (0-6 years) through the use of interactive number puzzles. This media provides a fun learning experience according to the principle of learning while playing, developing not only the ability to count but also the ability to think logically, understand patterns, categorize, and solve problems. Although effective, the use of this interactive media requires parental supervision and the ability of educators to operate the media properly. It can be concluded that interactive number puzzles are an effective learning strategy to foster logical mathematical intelligence in early childhood.